Exploratory outcomes of the DHA WIN randomized controlled trial: Supplementing women with docosahexaenoic acid did not reduce the impact of neoadjuvant breast cancer chemotherapy on quality of life or exercise behaviour - Claire M. Douglas; Marnie Newell; Susan Goruk; Kerry S. Courneya; Sunita Ghosh; Anil A. Joy; Jaqueline Munhoz; Catherine J. Field (PLoS ONE, 2025)
Supplementation of omega-3 (n-3) polyunsaturated fatty acids has been associated with reduced side effects and improved quality of life (QoL) in breast cancer patients receiving chemotherapy. The current study reports secondary outcomes from the DHA WIN randomized controlled trial which was designed to evaluate docosahexaenoic acid (DHA) supplementation (4.4 g/day) in conjunction with six cycles of neoadjuvant chemotherapy (NAC) (3 weeks/cycle) in women with non-metastatic breast cancer (n = 49). The objective of the current study was to assess the effects of DHA supplementation on QoL and exercise behaviour in women undergoing NAC for breast cancer. Self-administered questionnaires were used to measure QoL and exercise behaviour before starting chemotherapy (baseline), before each chemotherapy cycle (exercise), and after completing chemotherapy. DHA supplementation did not significantly affect QoL, aerobic exercise volume or resistance training frequency during treatment. However, mean aerobic exercise volume was significantly lower at week 12 (-53.5 minutes/week; 95% CI, -100.5 to -6.3; p = 0.02) and week 18 (-70.8 minutes/week; 95% CI, -123.0 to -18.6; p = 0.01) compared to baseline. Mean resistance training frequency was lower at week 12 (-0.57 times/week; 95% CI, -1.0 to -0.13; p = 0.02) compared to baseline. Meeting exercise guidelines during chemotherapy was not associated with better QoL. In the current exploratory study, QoL and exercise decreased during treatment regardless of DHA supplementation, highlighting the need for supportive care and potential therapies that may mitigate these declines in breast cancer patients receiving NAC. Adequately powered studies are needed to determine if DHA supplementation improves these two indices of health. The trial is registered at ClinicalTrials.gov (NCT03831178).